Efficacy Comparison of Intralesional inj.Interferon Alpha 2B (2 MU) against Intralesional Inj.Interferon Alpha 2B (3 MU) in Treatment of Peyronie’s Disease - Muhammad Zahid Ahmad, Muhammad Sabir Ashraf, Muhammad Asif, Nauman Ahmed, Shahjehan Khan, Aftab Ahmed Channa (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: In Peyronie’s Disease, fibrous plaque is formed which has an excessive amount of collagen, fibroblastic proliferation and elastin framework alteration. Objective: To compare the effect of Intralesional Inj.Interferon alpha 2b (2 MU) against Intralesional Inj. Interferon alpha 2b (3 MU) on plaque size, penile deviation, erectile function and pain during erection in patients having Peyronie’s disease Methods: It was comparative interventional/longitudinal study, conducted at Department of Urology, Kot Khawaja Saeed hospital, Lahore and Department of Urology, DHQ hospital Sheikhupura. Total 30 Patients of Peyronie’s disease in Urology OPD were enrolled. Patients were randomized into two groups by online random number generator. Results: In Group-A, after therapy, mean plaque length was decreased from 9.9±2.4 to 8.8±2.1 mm and mean plaque width was decreased from 4.2±0.9 mm to 3.8±0.4 mm, mean penile curvature was decreased from 34.1°±8.4° to 26.2°±7.2°, mean IIEF score was improved from 35.1±11.4 to 46.2±10.6, and mean pain score was decreased from 4.2±1.1 to 3.4±0.7. In Group-B, after therapy, mean plaque length was decreased from 10.7±2.6 to 7.3±1.8 mm and mean plaque width was decreased from 4.3±0.7 mm to 3.0±0.3 mm, mean penile curvature was decreased from 35.4°±7.9° to 20.1°±6.3°, mean IIEF score was improved from 36.3±12.4 to 59.8±12.6, and mean pain score was decreased from 4.1±1.0 to 1.9±0.6. Conclusion: Intralesional inj. Interferon alpha-2b (3MU) is more effective than Intralesional inj. Interferon alpha-2b (2MU) for reducing plaque size, pain, and penile deviation, and for improvement in erectile dysfunction in patients with Peyronie’s disease.